Tiktok Supplementary Instructional Media in Speaking Skill During Pandemic Covid-19 - Afidah, Nurul; Mutiara, Fanny Nanda (STKIP PGRI Ponorogo Press, 2021)
The objective of this study was to develop TikTok video content as supplementary instructional media in speaking class for students of MA. Unggulan KH. A. Wahab Hasbullah. ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model was adapted to develop the product. The video contained of 25 topics that discussed how to pronounce some similar words that have different pronunciation. Based on the validation of material experts and media experts, it could be seen that the results of material expert validation were 3.8 (good) and the results of media expert validation was 3.4 (good). 20 students of MA. Unggulan KHA. Wahab Hasbullah involved on implementation phase. The results of interviews with teachers and students overall showed good responses to the use of Tiktok video learning media in the learning process. Based on those results, it can be concluded that TikTok can help them in learning English especially in pronunciation aspects.